Laser welding of biodegradable polyglycolic acid (PGA) based polymer felt scaffolds - Rout, Soumya Sambit (Kansas State University, 2008)
Polyglycolic acid (PGA) is an important polymer in the field of tissue engineering. It has many favorable properties such as biocompatibility, bioabsorbability, high melting point, low solubility in organic solvents, high tensile strength and is used in a variety of medical related applications. Currently there are various methods such felting, stitching, use of binder/adhesive for joining the non woven meshes of PGA polymer in order to make suitable three dimensional scaffolds. The existing methods for joining the non woven meshes of PGA polymer are usually time consuming and not very flexible. Thus there is a need for a better technique that would overcome the drawbacks of the existing methods. Laser welding offers potential advantages such as high welding rates, easy to automate, improved seam and single sided access such that welds can be performed under various layers of fabric. Therefore, the main objective of this research is to conduct a fundamental study on laser welding of non woven PGA scaffold felts. An experimental setup for spot welding is built that would assist in the formation of tubular structures. A factorial design of experiments is used to study the effects of the operating parameters such as laser power, beam diameter, time duration and pressure on the weld quality. The weld quality is assessed in terms of weld strength and weld diameter. Based on the parametric study, a regression analysis is carried out to form correlations between weld quality and the operating parameters, which could be used to select the optimal operating conditions. The successful welds obtained by the laser welding process have no discoloration and are stronger than the tensile strength of the original non woven sheets of PGA biofelt.
Keywords: Laser welding; PGA polymer felts; Tubular scaffolds; Joining PGA felts; Engineering, Biomedical (0541); Engineering, Industrial (0546)